2019
DOI: 10.1175/jpo-d-18-0051.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Salinity-Stratified Bay of Bengal to Cyclone Phailin

Abstract: Cyclone Phailin, which developed over the Bay of Bengal in October 2013, was one of the strongest tropical cyclones to make landfall in India. We study the response of the salinity-stratified north Bay of Bengal to Cyclone Phailin with the help of hourly observations from three open-ocean moorings 200 km from the cyclone track, a mooring close to the cyclone track, daily sea surface salinity (SSS) from Aquarius, and a one-dimensional model. Before the arrival of Phailin, moored observations showed a shallow la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 69 publications
6
42
0
Order By: Relevance
“…Poststorm SSS salinification in the trail of TCs has already been extensively reported both from in situ and satellite observations (e.g., see Bond et al., 2011 ; Chaudhuri et al., 2019; Domingues et al., 2015; Grodsky et al., 2012; Lin et al., 2017; Liu et al., 2020; McPhaden et al., 2009; Price, 1981; Reul et al., 2014; Sanford et al., 1987; Steffen & Bourassa, 2018; Venkatesan et al., 2014; Vinayachandran et al., 2003; Yue et al., 2018; Zhang et al., 2016, 2018). SSS is generally expected to increase in the wakes of cyclones because subsurface water is on average saltier than surface water in the convective regions associated with cyclonic activity (Jourdain et al., 2013).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Poststorm SSS salinification in the trail of TCs has already been extensively reported both from in situ and satellite observations (e.g., see Bond et al., 2011 ; Chaudhuri et al., 2019; Domingues et al., 2015; Grodsky et al., 2012; Lin et al., 2017; Liu et al., 2020; McPhaden et al., 2009; Price, 1981; Reul et al., 2014; Sanford et al., 1987; Steffen & Bourassa, 2018; Venkatesan et al., 2014; Vinayachandran et al., 2003; Yue et al., 2018; Zhang et al., 2016, 2018). SSS is generally expected to increase in the wakes of cyclones because subsurface water is on average saltier than surface water in the convective regions associated with cyclonic activity (Jourdain et al., 2013).…”
Section: Introductionmentioning
confidence: 76%
“…To complement these first studies, we take advantage of the 10–years long period of satellite SSS products to present new insights and to more precisely document the ocean surface salinity response to TC passage, its global “mean” structure and associated variability. From L‐band radiometer measurements on‐board the Soil Moisture and Ocean Salinity (SMOS) and Soil Moisture Active Passive (SMAP) missions, accurate estimates of some large‐amplitude haline surface anomalies left in the wake of TCs have already been successfully demonstrated for several individual TC cases (Chaudhuri et al., 2019; Grodsky et al., 2012; Neethu, 2018; Reul et al., 2014; Yue et al., 2018). SSS retrievals in high wind conditions during the forced stage of TCs remain highly uncertain (Boutin et al., 2018; Meissner et al., 2018; Reul et al., 2020) and are therefore not considered in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies carried out by Chaudhuri et al () and Qiu et al () showed that salinity stratification and the presence of barrier layer could influence the surface cooling. Apart from the presence of warmer surface layers with approximately 80‐m thickness very near to the coast, salinity stratification may also have inhibited the cooling at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers explored TC‐induced oceanic responses through detailed case studies carried out on BoB TCs, namely, Sidr, Phailin, Nargis, Laila, Mala, and Jal, using both models (Prakash & Pant, ; Qiu et al, ; Vissa et al, ) and observations (Chaudhuri et al, ; Girishkumar et al, ; Maneesha et al, ; Vissa et al, ). The significant responses to TCs such as a decrease in sea surface temperature (SST), increase in salinity, mixed layer deepening, thermocline shoaling, enhanced heat loss to the atmosphere, and increase in chlorophyll‐a concentration are well documented (Price, ; Krishna et al, ; Sengupta et al, ; Vinayachandran & Mathew, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, little or no SST cooling is seen under the tracks of postmonsoon (October–November) tropical cyclones in the open ocean, mainly for two reasons: (i) the stable, shallow salinity‐dominated density stratification reduces the maximum depth of storm‐induced vertical mixing, and (ii) the mixing is confined to the nearly isothermal subsurface warm layer. It is likely that the very rapid intensification characteristic of many BoB cyclones (Mohapatra et al., 2015) is related to the temperature–salinity structure of the upper ocean (Balaguru et al., 2012; Chaudhuri et al., 2019; Neetu et al., 2012; Qiu et al., 2019; Sengupta et al., 2008; Vincent et al., 2014).…”
Section: Introductionmentioning
confidence: 99%